Possibility of producing ethanol by using moringa oleifera pods husk - Mohamad Zulfadzli, Jamaludin (2014)
Instead of using the conventional fuels, nowadays people are using biomass fuels such as ethanol to replace the conventional one like diesel and petrol because the fuels are having some shortage of sources problem and hiking in price. The shortage is due to time consumed during the drilling and processing from the underground until it passed through the piping system in order to fulfil demands from customers. Currently, researchers are developing the uses of biofuels for industrial and transportation purposes especially bioethanol. There are numerous raw materials that can be used in producing ethanol such as rice husk, com husk, wheat straw, millet husk, and also Moringaoleifera husk. This Moringaoleifera plant is a plant that has multifunctional uses. From its roots until the leaves, all of them can be used in medicinal prospects. The composition of cellulose, lignin and other components also similar to the composition of com husk which means it is possible to produce ethanol from this Moringaoleifera plant. In order to have a better quality of ethanol, few steps must be followed according to the researches did by past researchers. The steps that need to be followed are separated into three parts, pre-treatment of materials, hydrolysis process using alkaline technique with sodium hydroxide solution (NaOH), a fermentation process using Simultaneous Saccharification and Fermentation (SSaF) with enzymes and Saccharomyces cerevisiae yeast cells. For the last one is the analysis procedure of ethanol concentration to determine the different in concentration of ethanol produce in different parameter. The fermentation is done by manipulating the size of sample, concentration of yeast added, and pH value of sample which means the analysis is run after 72 hours of fermentation time. The ideal temperature for fermentation is 36°C and being put in the shaker at 150 rpm. The analysis method for detecting the presence of ethanol in the sample is by using a High Performance Liquid Chromatography (HPLC) with refractive index detector (Agilent 1200 Series Refractive Index Detector) and organic acid column (REZEX ROA-Organic Acid HPLC Column). 0.05 N Sulphuric acids (H2S04) is used as the solvent for this analysis. After 6 hours of running the analysis, the result was taken to be discussed further and based on the analysis and discussions, the sample of bigger size, 4.5 pH added with lg of yeast produced more ethanol concentration compare to the other parameter. The highest concentration produce is 0.007 g/L.